Borrelial lymphocytoma of the areola in a 9-year-old boy: a case report: Borelijski limfocitom areole pri devetletnem dečku: prikaz primera - Arko, Darja; Kavalar, Rajko; Takač, Iztok; Čas Sikošek, Nina; Gavrić Lovrec, Vida (Acta Medico-Biotechnica, 2023)
Purpose: This study presents a rare skin manifestation of Lyme borreliosis, specifically affecting the areola in a child in the absence of a history of a tick bite or erythema migrans. Case report: A 9-year-old boy presented with symptomless erythematous swelling of the breast areola for one month. Initial treatment for gynecomastia and then mastitis proved ineffective. A biopsy was performed, with histological findings revealing lymphocytoma, likely stemming from an insect bite. Serology for Borrelia burgdorferi was positive. Following a two-week course of oral amoxicillin, the lesion completely resolved. Conclusion: The consideration of Lyme disease should be a component of the differential diagnosis of skin lesions localised in typical areas, particularly in patients living in endemic regions.
Keywords: lymphocytoma, Lyme borreliosis, areola, histology